Demonstration Examination as a Form of Assessing the Formation of Professional Competences of Future Educational Psychologists - T.A. Egorenko; O.I. Leonova; I.A. Golovanova (Психологическая наука и образование)
The article contains an analysis of the normative and theoretical-methodological foundations of preparing and conducting a professional examination as a form of assessing the formation of professional competencies of future teacher-psychologists on the basis of the Center for Professional (Demonstration) Examinations of the Moscow State University of Psychology and Education. The study presents requirements for the development of the demonstrational exam and the criteria for its independent expert evaluation, the organizational process and stages of the professional (demonstrational) examination. The article concludes that interim and final certification, through professional (demonstrational) examinations, serves as an innovative method for assessing professional competencies. This approach not only evaluates the level of development of these competencies but also gauges the degree to which future educational psychologists have mastered the methods for solving professional problems. By addressing the current challenges associated with the preparation and administration of professional (demonstrational) examinations, we can enhance the quality of training for educational psychologists, ensuring it aligns with the demands of our time.